High-power, tunable source of coherent THz radiation driven by a microbunched electron beam - Konoplev, IV; Zhang, H; Doucas, G (IEEE, 2020)
"Pre-bunched"or "microbunched"charged particle beams have attracted significant interest in the last decade. Potential applications of such beams include development of the next generation of THz and X-ray light sources. This work presents the conceptual design of a tunable source of coherent Smith-Purcell THz radiation based on plasma-assisted pre-modulation of the continuous beam, and conditioning of the micro-bunched beam. The numerical simulations were carried out from the beam modulation to THz radiation generation using a self-consistent numerical model as well as a semi-analytical approach. Such a source would be a possible and useful alternative to conventional vacuum THz tubes and THz FEL sources.